Perlindungan Hukum Terhadap Pemegang Hak Eigendom Verponding Setelah Berlakunya Undang-Undang No 5 Tahun 1960 - Rabbani, Ahmad Rafi; Laturette, Adonia Ivonne; Radjawane, Pieter (Faculty of Law Universitas Pattimura, 2024)
ABSTRACT: Eigendom verponding is the right to land ownership which must be adjusted through the conversion provisions of the Basic Agrarian Law. The conversion was given a period of time until September 24, 1980. In practice, there is still recognition of land ownership of the former eigendom verponding which then occurs disputes over the land. Formulation of the problem in the study: . What is the legal status of unconverted eigendom verponding land. What is the legal protection for eigendom verponding land rights holders used by the government. The research method used is normative juridical, using a problem approach, namely a statutory approach, a conceptual approach and a case approach. The sources of legal materials used are primary, secondary, and tertiary legal materials. The technique of collecting legal materials used is the study of literature, journals, internet media, which is analyzed using qualitative methods. The results showed that legal protection for holders of land rights former eigendom verponding after the enactment of Law No. 5 of 1960 proof of ownership has not been converted until the period expires. But in Government Regulation No. 24 of 1997 concerning Land Registration, it is clear that until now the conversion of eigendom land can still be done through registration of old rights, so that its status changes to property rights. Efforts to resolve cases of ownership of eigendom verponding rights can be resolved in two ways, namely: litigation or non-litigation.